Current Treatment Approaches and Global Consensus Guidelines for Brain Metastases in Melanoma - Tan, Xiang-Lin; Le, Amy; Lam, Fred C.; Scherrer, Emilie; Kerr, Robert G.; Lau, Anthony C.; Han, Jiali; Jiang, Ruixuan; Diede, Scott J.; Shui, Irene M. (Frontiers in Oncology, 2022)
Background: Up to 60% of melanoma patients develop melanoma brain metastases (MBM), which traditionally have a poor diagnosis. Current treatment strategies include immunotherapies (IO), targeted therapies (TT), and stereotactic radiosurgery (SRS), but there is considerable heterogeneity across worldwide consensus guidelines. Objective: To summarize current treatments and compare worldwide guidelines for the treatment of MBM. Methods: Review of global consensus treatment guidelines for MBM patients. Results: Substantial evidence supported that concurrent IO or TT plus SRS improves progression-free survival (PFS) and overall survival (OS). Guidelines are inconsistent with regards to recommendations for surgical resection of MBM, since surgical resection of symptomatic lesions alleviates neurological symptoms but does not improve OS. Whole-brain radiation therapy is not recommended by all guidelines due to negative effects on neurocognition but can be offered in rare palliative scenarios. Conclusion: Worldwide consensus guidelines consistently recommend up-front combination IO or TT with or without SRS for the treatment of MBM.